CRITICAL LITERATURE REVIEW: THE EFFECT OF MACHIAVELLIAN MARKETING IN THE CONTEXT OF SOCIAL MEDIA AND E-COMMERCE USE ON THE PURCHASING BEHAVIOR OF MILLENNIALS AND GENERATION Z - Junianto, Pilifus; Irawan, Agustinus Purna (International Journal of Application on Economics and Business, 2025)
In recent decades, the development of information and communication technology has profoundly transformed the marketing landscape. Social media has emerged as a dominant platform used by marketers to reach consumers, particularly among Millennials and Generation Z, who are active users of digital technology. This study examines the impact of Machiavellian Marketing strategies on the purchasing behavior of Millennials and Generation Z through social media and e-commerce platforms. Machiavellian Marketing, characterized by manipulative and often unethical approaches, exploits the digital habits and psychological tendencies of these young consumers. Furthermore, this study highlights the influence of Dark Triad personality traits—Machiavellianism, narcissism, and psychopathy—on consumer behavior. Individuals with high levels of these traits are known to be more prone to engage in manipulative behavior on social media, which affects their purchasing decisions. The research was conducted through a literature review method from the Scopus database, aiming to provide critical insights into the ethical implications of Machiavellian-based marketing strategies as well as offering new perspectives on ethics in result-oriented marketing. These findings are expected to aid marketers in designing strategies that align with the psychological profiles of consumers while considering their ethical implications.